IMPLEMENTATION OF HYPERTEXT TO IMPROVE STUDENTS’ UNDERSTANDING IN ENGLISH READING - Ratna Said; Firman Alamsyah Mansyur (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2019)
This research aimed to determine the implementation of hypertext which can improve students’ understanding in English reading. This research is action research. conducted in a class by carrying out stages such as planning, implementing, and reflecting on collaborative and participatory actions to improve performance as a lecturer so that student learning outcomes can improve. Despondences are the students are in class E even semester of 2018/2019 academic year. The result showed the ability of students to understand English reading has increased through hypertext media where the highest score is 93, the lowest score is 60 with an average of 74.5. With the details of 8 students scoring 93, 10 students scoring 76, 6 students scoring 69 and 4 students scoring 60.